2021
DOI: 10.1097/pcc.0000000000002813
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Following Delirium in the PICU*

Abstract: To evaluate whether delirium during pediatric critical illness is associated with post-discharge health-related quality of life. DESIGN: Retrospective cohort study. SETTING: Academic tertiary care center. PATIENTS: Children 1 month to 18 years old admitted to the PICU or cardiac ICU and enrolled in the Seattle Children's Hospital Outcomes Assessment Program. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS:Delirium was assessed twice daily using the Cornell Assessment of Pediatric Delirium; a score greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The total scores were transformed to a linear scale ranging from 0–100, with higher scores indicating better HRQL. A numeric score assessed by either scale indicated the same HRQL consistent with prior PICU outcomes research 5,18–19 …”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…The total scores were transformed to a linear scale ranging from 0–100, with higher scores indicating better HRQL. A numeric score assessed by either scale indicated the same HRQL consistent with prior PICU outcomes research 5,18–19 …”
Section: Methodsmentioning
confidence: 86%
“…The OAP collected HRQL data for all consenting participants admitted to the PICU from December 2011 to February 2017. The OAP has been used to examine the associations between HRQL and critical illness and has been described in detail in prior publications 5–6 . Seattle Children's is a freestanding academic children's hospital with 334 inpatient beds, including 32 PICU beds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data to long-term outcomes associated with pediatric delirium are rare. Two authors found an association between delirium during the PICU stay with decline in health-related quality of life (10,11). Evidence on measures to prevent and manage delirium is urgently needed.…”
Section: Introductionmentioning
confidence: 99%